Analysis of Price Factors and Business Competition in The Covid-19 Pandemic NN Efforts to Increase Sales Volume - Novaliana, Ika; Mahendra, Prasetya Tri (Future Science / FSH-PH Publications, 2023)
The aims of this study are: (1) To find out and prove the effect of price during the covid-19 pandemic on sales volume, (2) To find out and prove the effect of business competition during the COVID-19 pandemic on sales volume, (3) To find out and prove Simultaneous effect of price and business competition during the COVID-19 pandemic on sales volume. Data analysis was carried out by quantitative descriptive analysis with a sample size of 80 people who stated that the study had a population of 100. The results showed that: (1) Based on the t-test, the tcount value was 4.432 while the ttable value was 1.990. It is proven that there is a positive and significant effect between price and sales volume, (2) Based on the t-test, the t-value is 3.893 while the t-table value is 1.990. It can be interpreted that the business competition variable partially has a positive and significant effect. The contribution of price and business competition to sales volume is 33.4%.